Antenatal Glucocorticoids Reduce the Incidence of Refractory Hypotension in Low Birthweight Infants during the Early Neonatal Period, but Do Not Affect It beyond This Time - Tomotaki, Seiichi; Iwanaga, Kougoro; Hanaoka, Shintaro; Tomotaki, Hiroko; Matsukura, Takashi; Niwa, Fusako; Kawai, Masahiko (American Journal of Perinatology, 2020)
Objective This study aimed to clarify the effect of antenatal glucocorticoids (AGs) on the incidence of refractory hypotension (RH) in very low birthweight (VLBW) infants after the first week of life.Study Design We included VLBW infants born at a gestational age of <30 weeks and divided them into three groups: the complete group (born within 7 days of completing a single course [two doses] of AGs), the incomplete group (born without complete course), and the late delivery group (born at ≥8 days after a single course). We compared the incidence and period of onset of RH among the three groups.Results A total of 115 infants were enrolled. The incidence of RH in the first week of life was significantly lower in the complete group than in the other groups. However, there was no significant difference in the incidence of RH after the first week of life among the groups.Conclusion AGs contribute to circulatory stabilization during the first week of life, but this effect does not last after 1 or 2 weeks of administration. In infants who receive AGs, physicians should consider that the risk of RH after the first week of life is not low.
Keywords: adrenal insufficiency; betamethasone; blood pressure; hypothalamic–pituitary–adrenal axis; preterm